A GLOBAL STUDY OF TRANSITION ZONE THICKNESS USING RECEIVER FUNCTIONS - Lawrence J.F.; Shearer P.M. (My University, 2006)
Systematic stacks of P wave receiver functions (Pds) for 118 global seismic stations yield new transition zone thickness (WTZ) estimates, as measured by the difference in depths between the 410- and 660-km mantle discontinuities. The receiver functions are computed from high signal-to-noise records of earthquakes between 1976 and 2002 recorded at distances of 30° to 90°. We obtain a globally averaged transition zone thickness of 242 ± 2 km, in good agreement with SS precursor (Sds) results. Previously noted differences in average WTZ between Pds and SdS studies are caused by both geographic bias and the constant ray parameter approximation used in many prior Pds studies, which causes a ~4 km overestimation of WTZ. Pds observations suggest lateral variations in WTZ of ±20 km with maximal variations of ±35 km and a long-wavelength topography pattern that agrees with SS precursor results showing thick WTZ beneath cold subduction zones and thin WTZ beneath warmer regions. Copyright 2006 by the American Geophysical Union.